2018
DOI: 10.3354/dao03193
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of eastern water dragons Intellagama lesueurii lesueurii to Bohle iridovirus

Abstract: Ranaviruses infect and have been associated with mass mortality events in fish, amphibians and reptiles and are capable of interclass transmission. Eastern water dragons (EWDs), a semi-aquatic squamate, have an overlapping distribution with several species shown to be susceptible to Bohle iridovirus (BIV). However, this species has not been previously investigated, and no known mass mortalities have occurred in wild populations. Here we report the experimental infection of juvenile EWDs with BIV to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…Similarly, i.m. inoculated eastern water dragons (EWDs) succumbed to infection more quickly than the hatchlings in this study [22]. EWDs developed clinical signs between 1-5 days and mortalities occurred 5-8 days post-inoculation with 10 5.33 TCID 50 ml −1 BIV, whereas the turtles developed clinical signs between 14-30 days and mortalities occurred 16-24 days post-inoculation with the same dose.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Similarly, i.m. inoculated eastern water dragons (EWDs) succumbed to infection more quickly than the hatchlings in this study [22]. EWDs developed clinical signs between 1-5 days and mortalities occurred 5-8 days post-inoculation with 10 5.33 TCID 50 ml −1 BIV, whereas the turtles developed clinical signs between 14-30 days and mortalities occurred 16-24 days post-inoculation with the same dose.…”
Section: Discussionmentioning
confidence: 65%
“…The BIV isolate used in this study was produced according to the methods of Maclaine et al [22]. Briefly, fathead minnow (FHM) cells were used to propagate the isolate at 25 °C.…”
Section: Source Of Virusmentioning
confidence: 99%
“…Histological examination revealed that the condition was largely confined to the epidermis, while all other organs in the animals investigated appeared normal. Skin lesions associated with ranaviral infection have been reported in lizards and turtles, but in most cases internal organs were also infected (29)(30)(31)(32). While there was no detectable bias toward sex or species of turtles, the odds ratio indicates that the larger the turtle, the higher the risk of a lesion, and juveniles were rarely affected.…”
Section: Characteristics Of the Lesionsmentioning
confidence: 91%
“…The hatchlings of both species of freshwater turtles were susceptible to infection via intra-coelomic exposure although oral inculcation was not attempted. Juvenile Australian eastern water dragons (Intellagama lesueurii lesueurii) developed ranaviral disease from all exposure routes tested (oral, intramuscular, and cohabitation) (Maclaine et al, 2018). Differences in susceptibility via different routes of exposure may reflect real differences in natural transmission routes between reptiles and other Classes.…”
Section: Transmissionmentioning
confidence: 99%
“…Using total IgY levels as an internal control may minimise diagnostic errors resulting from seasonal variations in antibody levels. PCR based assays have been used conventionally and in quantitative real-time assays to detect reptilian ranaviruses in a number of sample types including blood, oral and cloacal swabs, and fresh and fixed tissues (Pallister et al, 2007;Allender et al, 2013a;Goodman et al, 2013, Butkus et al, 2017Leung et al, 2017;Maclaine et al, 2018). Molecular surveys of turtle populations for ranavirus have revealed that swabs and blood samples are not equally valid targets for ranavirus detection (Allender et al, 2013a).…”
mentioning
confidence: 99%